2020
DOI: 10.1002/jtr.2391
|View full text |Cite
|
Sign up to set email alerts
|

The influence of neophobia and enduring food involvement on travelers' perceptions of wellbeing—Evidence from international visitors to Iran

Abstract: This study adopts PERMA as the theoretical lens to analyze the influence of neophobia (reluctance to try new food) and enduring involvement on travelers' perceptions of the contribution of authentic food experiences to their well-being. Based on a survey of international visitors to Iran, the results show that authentic food experiences are strongly associated with positive emotions and meaningfulness of a trip. Higher food involvement and lower neophobia are associated with stronger perceptions that authentic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 84 publications
1
33
0
Order By: Relevance
“…Third, it was found that it is important to provide novel tastes and appealing flavors, particularly for tourists who show low neophobia; that is, those who actively seek exotic and unusual local food experiences (Caber et al , 2018; Lai et al , 2020; Mak et al , 2017; Pourfakhimi et al , 2021). In this regard, DMOs should continue to collaborate with stakeholders and food vendors on the need to incorporate significant aspects of their destinations’ culture in the selection of ingredients, cooking and serving to enhance the authenticity and taste of local foods to improve tourists’ overall experiential quality.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Third, it was found that it is important to provide novel tastes and appealing flavors, particularly for tourists who show low neophobia; that is, those who actively seek exotic and unusual local food experiences (Caber et al , 2018; Lai et al , 2020; Mak et al , 2017; Pourfakhimi et al , 2021). In this regard, DMOs should continue to collaborate with stakeholders and food vendors on the need to incorporate significant aspects of their destinations’ culture in the selection of ingredients, cooking and serving to enhance the authenticity and taste of local foods to improve tourists’ overall experiential quality.…”
Section: Discussionmentioning
confidence: 99%
“…There is also a need for further exploration of the structural relationships between MLFCEs and other outcome variables such as overall satisfaction with the travel experience, image of the destination, place attachment and familiarity with the destination. Furthermore, there is a need to investigate the moderating functions of other factors such as food personality (Ji et al , 2016; Kim et al , 2010; Mak et al , 2017), food involvement (Caber et al , 2018; Pourfakhimi et al , 2021) and food consumption value (Choe and Kim, 2018) in understanding the sign or magnitude of the relationships between international diners’ MLFCEs and their evaluations. Finally, a qualitative study should be undertaken to confirm the findings of this study, since in-depth interviews can help to explain the hermeneutic nature of the reasoning behind tourists’ memorable local food experiences and their consequences.…”
Section: Limitations and Suggestions For Future Researchmentioning
confidence: 99%
“…The popularity of this "foodism" fuels the growing demand for diverse, innovative, meaningful and engaging culinary leisure experiences (Prayag et al, 2020), with workshops and cooking classes now serving as core destination attractions (Genc, 2017). Meaningful food experiences can, therefore, enhance consumer well-being (Pourfakhimi et al, 2020), with increasing attention paid to service design in the hope of stimulating memorable consumption (Genc, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Various avenues are highlighted to exploit the vast commercial halal food market in non-Muslim majority destinations. Questionnaire survey, structural equation modelling (SEM), confirmatory factor analysis (CFA) [ 112 ] (2021) neophobia and well-being The results show that having an authentic food experience is most strongly associated with the sense of meaningfulness of the trip and experiencing positive emotions during the trip. Enduring food involvement can explain both hedonic and eudaimonic aspects of the degree of the impact of food experiences on well-being.…”
Section: Table A1mentioning
confidence: 99%